2010
DOI: 10.1016/j.jbiomech.2010.03.015
|View full text |Cite
|
Sign up to set email alerts
|

A knee-specific finite element analysis of the human anterior cruciate ligament impingement against the femoral intercondylar notch

Abstract: This work presents a finite element analysis of Anterior Cruciate Ligament (ACL) impingement against the intercondylar notch during tibial external rotation and abduction, as a mechanism of noncontact ACL injuries. Experimentally, ACL impingement was measured in a cadaveric knee in terms of impingement contact pressure and six degrees-of-freedom tibiofemoral kinematics. Three-dimensional geometries of the ACL, femur and tibia were incorporated into the finite element model of the individual knee specimen. A fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 24 publications
0
37
0
Order By: Relevance
“…A majority of these models are static or quasi-static in nature [20,[24][25][26]28,29,[31][32][33]37,38,[40][41][42], typically focused on isolated tibiofemoral joint missing the patellofemoral interaction [22,25,26,37,38,40,41]. Further, a number of simphfying assumptions such as lack of anatomical representation of menisci [19,22,25,27,37,38,40,41], articular cartilage [19,22,37,38,41], and other connective tissue [26,[31][32][33]37,38,40,41] are associated with some of the existing models. Also, in most cases, connective tissues are modeled by uniaxial discrete line elements (truss or spring elements) with simplified material properties [19,20,[23][24][25]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A majority of these models are static or quasi-static in nature [20,[24][25][26]28,29,[31][32][33]37,38,[40][41][42], typically focused on isolated tibiofemoral joint missing the patellofemoral interaction [22,25,26,37,38,40,41]. Further, a number of simphfying assumptions such as lack of anatomical representation of menisci [19,22,25,27,37,38,40,41], articular cartilage [19,22,37,38,41], and other connective tissue [26,[31][32][33]37,38,40,41] are associated with some of the existing models. Also, in most cases, connective tissues are modeled by uniaxial discrete line elements (truss or spring elements) with simplified material properties [19,20,[23][24][25]…”
Section: Introductionmentioning
confidence: 99%
“…Such an assumption of soft tissue geometry may be useful in the investigation of joint kinematics. However, this assumption is associated with shortcomings such as the inability to predict nonuniform 3-dimensional (3D) stresses and strains across the tissue [27,29,31,41]. Considering the fact that the accuracy in FE model predictions depends directly on assumptions made in the model, an anatomically accurate 3D representation coupled with realistic constitutive models is needed to simulate the complex nature of these structures [27,29,31,37,41].…”
Section: Introductionmentioning
confidence: 99%
“…A number of investigators have used force driven analyses to understand the stresses within the knee joint soft tissues (Haut Donahue et al 2003;Peña et al 2006;Kiapour et al 2014). Studies have also used displacement driven analyses to study the knee joint soft tissue stresses (Gardiner and Weiss 2003;Song et al 2004;Park et al 2010). The boundary conditions for these displacement controlled simulations are generally extracted from cadaver experiments.…”
Section: Methodsmentioning
confidence: 99%
“…requiring quadriceps force with a neutral knee position) alone failed to exceed 2000N of load on the ACL, whereas a combined valgus load and quadriceps force resulted in exceeding the tensile strength of the ACL. Park et al [217] provided unique perspectives on the effects of multi-planar loading. Finite element analysis showed that impingement between the ligament and the lateral wall of intercondylar notch could occur when the knee at 45° was externally rotated at 29.1° and abducted at 10°.…”
Section: Computational Simulationmentioning
confidence: 99%